PENGUATAN KAPASITAS KEUANGAN NEGARA MELALUI REVISI UU PENGELOLAAN PNBP - Ariesy Tri Mauleny (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2017)
One of the government’s duties and functions in the state finance is the management of state revenue as a source of development financing. Efforts to maintain fiscal stability through increased state revenues have not been fully supported by optimal non-tax government revenue or so called locally as PNBP management. This can be seen from PNBP achievement which is still fluctuative and the correlation to the economic growth and the achievement of development indicators have not yet been shown added to the various problems that occurred in 20 years of PNBP management since the enactment of Law Number 20/1997 that demanded the completion of the Draft Law on PNBP Management. This makes this study interesting to be examined. The use of qualitative analysis and descriptive approach are expected to be able to describe the mapping of PNBP management’s problem comprehensively and to present strategic issues in the PNBP Management Bill discussion so that the strengthening of state finances can be achieved through PNBP management revision. The draft law existence on PNBP is also expected to provide legal clarity, legal certainty, legal enforceability and legal effectiveness for central and local government in manifesting decentralization that justify, effective and efficient. Discussion of PNBP’s draft law is to involve local government, which is the one that wil create PNBP and to focus on its mechanism of management.